Study on the hybrid energy storage for industrial park energy systems: Advantages, current status, and challenges - Guo Jiacheng; Peng Jinqing; Luo Yimo; Zou Bin; Luo Zhengyi (National Science Open)
In order to increase the renewable energy penetration for building and industrial energy use in industrial parks, the energy supply system requires transforming from a centralized energy supply mode to a distributed + centralized energy supply mode. The application of a hybrid energy storage system can effectively solve the problem of low renewable energy utilization levels caused by a spatiotemporal mismatch between the energy source and load. This study summarized the advantages and limitations of common energy storage technologies in industrial parks from the aspects of service life, response time, cycle efficiency and energy storage density, etc. The advantages of the hybrid energy storage system in industrial parks were also discussed in terms of sustainable development, climate change mitigation, social impact, and other aspects. The typical frameworks of hybrid energy storage were summarized, and the advantages, disadvantages, and application scenarios of each typical framework were analyzed. The current status of hybrid energy storage systems was summarized from the aspects of system modeling, hybrid energy storage mechanisms, design optimization, and operation dispatching. At the same time, the key challenges in modeling, regulation, and optimization of hybrid energy storage systems were discussed. This discussion leads to proposals for the direction of future research. The optimization methods and processes for designing and operating hybrid energy storage systems were proposed based on theoretical frameworks and methods. It is hoped that this review can provide some guidance and serve as a reference for developing and applying hybrid energy storage systems in industrial parks.